Analisis Kemampuan Pemecahan Masalah Siswa dalam Menyelesaikan Soal Numerasi Ditinjau Berdasarkan Kemampuan Matematika - Setyorini, Ayu; Nuriyatin, Siti; Sukriyah, Dewi (Jurnal Riset Pembelajaran Matematika, 2024)
This study aims to describe students' problem solving skills in solving numeracy problems on flat building material. This type of research is descriptive qualitative. This research was conducted at MTs Ma'arif NU Ngaban-Tanggulangin class VII in the 2024/2025 school year. The research subjects were selected based on the recommendation of the math subject teacher. Three students consisting of one high ability student, one medium ability student, and one low ability student were selected based on the daily grades of students in class VII-D MTs Ma'arif NU Ngaban Tanggulangin. The instruments used are test questions consisting of three questions and interview sheets. In problem solving using Polya's problem solving stages which consist of four indicators, namely 1) understanding the problem. 2) solution plan. 3) solving the problem. 4) re-examine the answer. Data analysis techniques used are data collection techniques, data reduction techniques, data presentation techniques and making conclusions. Interviews were used to ensure the accuracy of the data. The results of the study are based on Polya's stages, high ability students are able to fulfill all stages of Polya in solving problems. Medium ability students were able to fulfill Polya's stages but still unable to make conclusions and re-examine their answers. Low ability students are only able to understand the problem, not yet able to do the next stage.